KESADARAN BUDAYA PELAJAR DWIBAHASA: STUDI KASUS YANG DIKONTEKSTUALISASIKAN DI SEBUAH PESANTREN - Khittotun Nahidin (Mastery: Master of English Language Journal, 2023)
This study aims to explore cultural awareness of bilingual learners in the unique context of an Islamic boarding school. It focuses on how they manage their cultural identities, both in the Islamic framework and in the broader multicultural context. This study uses qualitative research method, including semi-structured interview, observation, and document analysis in order to explore the cultural experiences, challenges, and strategies employed by these learners. The findings reveal the nuanced ways in which cultural awareness shapes the language acquisition process for bilingual learners. Moreover, it highlights the significance of creating culturally sensitive pedagogical approaches that accommodate the needs of learners in Islamic boarding schools. This research contributes to the broader discourse on bilingual education, cultural awareness, and the role of religious institutions in shaping the learners’ cultural identity. In addition, it offers valuable insights for teachers or educational stakeholders seeking to foster inclusive and culturally relevant educational environments in diverse settings.